2012
DOI: 10.1002/eji.201141821
|View full text |Cite
|
Sign up to set email alerts
|

Invariant natural killer T cells are not affected by lysosomal storage in patients with Niemann‐Pick disease type C

Abstract: Summary Invariant Natural Killer T (iNKT) cells are a specialised subset of T cells that are restricted to the MHC class I like molecule, CD1d. The ligands for iNKT cells are lipids, with the canonical superagonist being α-galactosylceramide, a non-mammalian glycosphingolipid. Trafficking of CD1d through the lysosome is required for the development of murine iNKT cells. Niemann-Pick type C (NPC) disease is a lysosomal storage disorder caused by dysfunction in either of two lysosomal proteins, NPC1 or NPC2, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
(35 reference statements)
1
16
1
Order By: Relevance
“…On the basis of the hypothesis that pAg þ stimulatory cells could be involved in transferring APC characteristics, we considered that although EBV-B cells are known to be capable of presenting antigen via MHC class I and II, their CD1d-restricted antigen-presenting capacities are compromised as EBV-B cells in vitro often downregulate CD1d expression on their cell surface and are thus relatively poor in presenting a-GalCer to iNKT cells (19,20). antigen CD19 could be observed (Fig.…”
Section: A-galcer-pulsed Pag-activated Vg9vd2-t Cells Do Not Trigger mentioning
confidence: 99%
“…On the basis of the hypothesis that pAg þ stimulatory cells could be involved in transferring APC characteristics, we considered that although EBV-B cells are known to be capable of presenting antigen via MHC class I and II, their CD1d-restricted antigen-presenting capacities are compromised as EBV-B cells in vitro often downregulate CD1d expression on their cell surface and are thus relatively poor in presenting a-GalCer to iNKT cells (19,20). antigen CD19 could be observed (Fig.…”
Section: A-galcer-pulsed Pag-activated Vg9vd2-t Cells Do Not Trigger mentioning
confidence: 99%
“…Defects in iNKT cell populations have been reported in mouse models of lysosomal storage diseases (28,56,60), and it has been suggested that lysosomal storage per se may induce defects in mouse CD1d antigen presentation through spatial restrictions in the endocytic system and not necessarily because antigens are absent. However, this does not seem to be the case for human CD1d because iNKT cells levels are normal in Niemann-Pick disease type C and Fabry patients, which might be the result of the differences in intracellular trafficking of mouse and human CD1d molecules (61,62). LPLA2 is a lysosomal enzyme, and its absence induces phospholipidosis in alveolar and peritoneal macrophages (50); thus, reduced stimulation by Lpla2…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in Gaucher and Fabry disease patient, analyzed “iNKT-like” cells by the use of an antibody against Vα24 TCR α-chain, and no differences were observed between patients and controls [67,68,69]. Subsequent studies determined the frequency of iNKT cells in the peripheral blood of Fabry, Gaucher, and NPC disease patients, and no alterations in iNKT cell frequency were detected when compared with control subjects [13,70,71]. This can be attributed to the different trafficking pathways between human and mouse CD1d.…”
Section: Lysosomal Storage and Nkt Cellsmentioning
confidence: 99%